When East met West - Tuttle, W. C. (Wilbur C.), 1883-1969 (Salt Lake City, UT : Project Gutenberg, 2024)
"When East Met West" by W. C. Tuttle is a complete novelette written in the early 20th century. This humorous work is set in the American West, specifically in the small, quirky town of Piperock, and explores the comical interactions between its eccentric residents. With a blend of satire and adventure, the central theme revolves around local pride, ambition, and the absurd ideas that spring up when the townsfolk seek to improve their image and attract visitors. The story follows protagonists Ike Harper and Dirty Shirt Jones as they return from a prospecting trip to find that their friend Magpie Simpkins has taken on the role of president of the newly founded Piperock Chamber of Commerce. Magpie's grand ambitions for the town include acquiring a zoo with exotic animals to draw in crowds and elevate Piperock's status. However, a series of farcical events unfold, including animal escapes and a chaotic Labor Day celebration that pits Piperock against the neighboring town of Paradise. Ultimately, the narrative showcases the humorous excesses of small-town politics, civic pride, and the ludicrous lengths to which people will go to claim success and recognition. The comedic tone, vivid characters, and outrageous plot make this book an entertaining read for those who enjoy light-hearted Western humor. (This is an automatically generated summary.)
Release date is 2024-12-21
Roger Frank and Sue Clark
Keywords: Animals -- Fiction; Western stories; Simpkins, Magpie (Fictitious character) -- Fiction; Harper, Ike (Fictitious character) -- Fiction; Piperock (Montana : Imaginary place) -- Fiction